Intestinal current measurement detects age-dependent differences in CFTR function in rectal epithelium - Gräber, Simon Y.; Sommerburg, Olaf; Yu, Yin; Berges, Julian; Hirtz, Stephanie; Scheuermann, Heike; Berger, Jasmin; Duerr, Julia; Mall, Marcus A. (Frontiers in pharmacology, 2025)
Intestinal current measurement (ICM) provides a sensitive bioassay for assessment of cystic fibrosis transmembrane conductance regulator (CFTR) function in rectal biopsies ex vivo and is used as a diagnostic tool for cystic fibrosis (CF). Furthermore, ICM was shown to be sensitive to detect pharmacological rescue of CFTR function by CFTR modulators in people with CF carrying responsive CFTR mutations. Results from clinical trials of CFTR modulators across age groups indicate that CFTR function in the sweat duct may be age-dependent with children reaching higher levels than adults. However, little is known about age dependency of CFTR function in the intestinal epithelium.